Analisis Implementasi Dan Optimalisasi Penerimaan Pajak Bumi Dan Bangunan (Pbb) Dalam Peningkatan Pendapatan Asli Daerah Di Kabupaten Manokwari - Jemi Awi Mandacan; Ardiansya Ardiansya (Benefit: Journal of Bussiness, Economics, and Finance, 2025)
This research aims to analyze the implementation and optimization strategies of Land and Building Tax (PBB) revenue in enhancing Local Government Revenue (PAD) in Kabupaten Manokwari. This study employs a qualitative research method with a descriptive-analytical approach through literature studies and analysis of secondary data related to PBB revenue. The results show that PBB revenue in Kabupaten Manokwari has increased from 2022 to 2024, yet there remains a gap between the target and actual revenue in various regions. Factors causing low PBB collection include lack of socialization, economic capability of the community, inaccurate taxpayer data, and low taxpayer awareness. This study finds that the implementation of various policies and PBB optimization strategies, including data updates, service quality improvement, and modernization of tax administration, can significantly increase PBB revenue, which impacts the enhancement of PAD. This research recommends strengthening coordination among related institutions, improving human resource capacity, and developing integrated tax information systems to optimize PBB revenue.